1989
DOI: 10.2118/15399-pa
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of L1/L2/V Behavior in CO2/Hydrocarbon Systems

Abstract: Summary The temperature dependence of liquid/liquid (L1/L2) and liquid/liquid/vapor (L1/L2/V) phase behavior in CO2 /hydrocarbon systems is investigated with a combination of measurement of L1/L2 and L1/L2/V phase compositions and calculations of two- and three-phase behavior with the Peng-Robinson equation of state (PREOS). New phase-composition data are reported for mixtures of CO2 with normal hexadecane (C16) and squalane (C30) and for mixtures of CO2 with methane (C1) and hexadecane. Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 27 publications
2
20
0
1
Order By: Relevance
“…Thus, the experimental evidence for extraction is consistent with the appearance of three phases as long as the temperature is not too far above 880F (3 I°C), the critical temperature of CO2. The results shown here are also consistent with the analyses of Orr and Jensen (1984) and Larsen et al (1989), who showed that if three phases appear, they will do so in the neighborhood of the extrapolated vapor pressure of CO2. It is interesting to note, however, that the MMP for this oil, reported by Magruder et al (1990) to be between 1850 and 2300 psia, is significantly higher than that of the oil examined by Orr and Jensen.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the experimental evidence for extraction is consistent with the appearance of three phases as long as the temperature is not too far above 880F (3 I°C), the critical temperature of CO2. The results shown here are also consistent with the analyses of Orr and Jensen (1984) and Larsen et al (1989), who showed that if three phases appear, they will do so in the neighborhood of the extrapolated vapor pressure of CO2. It is interesting to note, however, that the MMP for this oil, reported by Magruder et al (1990) to be between 1850 and 2300 psia, is significantly higher than that of the oil examined by Orr and Jensen.…”
Section: Discussionsupporting
confidence: 91%
“…Several observations of Vapor-Liquid-Liquid Equilibrium (VLLE) phase behavior in oil-CO 2 systems have been reported in literature (Huang et al (1974), Shelton et al (1977), Metcalfe et al (1979), Yellig (1981), Orr et al (1981), Turek et al (1984), Larson et al (1989), and Stalkup (1992)). A further complexity may arise when the addition of CO 2 leads to precipitation of asphaltenes from the oil, which is either reported as a VLLE or more commonly as a Vapor-Liquid-Solid Equilibrium (VLSE) system.…”
Section: Introductionmentioning
confidence: 97%
“…It should also be observed that the SWEOS and the PREOS interaction parameters are very similar, except for n-alkanes heavier than 0 16 . This implies that the interaction parameters determined for the PREOS could be used in the SWEOS and vice versa.…”
Section: Resultsmentioning
confidence: 81%
“…al. 16 found that it is particularly important that binary interaction parameters be chosen to match some L-L data.…”
Section: Calculationsmentioning
confidence: 99%